THE EFFECT OF INSTAGRAM SOCIAL MEDIA PROMOTION OPTIMIZATION ON SALES VOLUME AT GALLERY RAJUT BANDUNG - Diawati, Prety; Abdulghopar, Obay; Suarsa, Senny Handayani (STIE Pelita Nusantara Semarang, 2025)
The advancement of digital technology has transformed the marketing landscape, making social media one of the primary channels for product promotion. This study aims to determine the effect of optimizing Instagram social media promotion on the sales volume of Gallery Rajut Bandung. Using a quantitative associative descriptive method, data were collected through questionnaires from 75 people who are work with Gallery rajut bandung. The independent variable is Instagram social media promotion, measured by content creation, content sharing, connecting, and community building indicators, while the dependent variable is sales volume, measured through sales growth, profit, and the number of customers. The results of a simple linear regression analysis indicate that Instagram social media promotion has a positive and significant effect on sales volume. Optimizing digital promotion strategies, such as improving content quality, posting consistency, and collaborating with influencers, is recommended to support sustainable sales growth.